The effectiveness of the psychological intervention “Problem Management Plus” in managing neurotic and stress-related disorders - Сумарюк, Богдан; Юрценюк, Ольга (Психосоматична медицина та загальна практика, 2025)
Introduction. The majority of the Ukrainian population has been affected by factors detrimental to well-being and mental health due to the ongoing war. As part of the national mental health program “How Are You?” initiated by First Lady Olena Zelenska, a recent study indicated a steady decline in Ukrainians’ satisfaction with their own mental health. According to a nationwide survey conducted in December 2024 – January 2025, only 21% of respondents reported being satisfied with their mental health, while 44% expressed dissatisfaction. The war and related challenges remain the primary source of psychological strain: 83% of participants reported high stress levels, and 78% explicitly linked their distress to the full-scale russian invasion (HowAreU, 2025). Financial hardship affects 52% of the population, while 47% are concerned about the socio-political situation. High levels of fatigue, tension, fear, and irritability persist, alongside emotional states indicative of psychological distress, including helplessness, frustration, and despair. These findings highlight the urgent need for accessible and effective interventions targeting distress-related conditions, especially short-term, evidence-based psychological approaches for adults in communities facing adversity (HowAreU, 2025). In response to the global mental health crisis, the World Health Organization (WHO) developed Problem Management Plus (PM+), a low-intensity psychological intervention for individuals experiencing distress. Given the rising prevalence of stress-related mental disorders in Ukraine — particularly in the context of the ongoing war — data from the National Health Service of Ukraine (NHSU) confirm this trend. The number of diagnosed post-traumatic stress disorder (PTSD) cases rose from 3,167 in 2021 to 7,051 in 2022, and 12,494 in 2023. As of March 6, 2024, 3,292 PTSD cases had already been registered (NHSU, 2024). Our study on the prevalence of neurotic and stress-related disorders among volunteers during wartime revealed that 28.47% of the 288 participants met the ICD-10 diagnostic criteria for disorders under F40–F48 “Neurotic, stress-related and somatoform disorders”, (Sumariuk & Yurtseniuk, 2024). WHO estimates that approximately 22% of individuals exposed to war or conflict in the past decade will experience mental disorders such as depression, anxiety, PTSD, or related conditions (WHO, 2022). These figures underscore the necessity for scalable psychological interventions to support mental health and prevent distress — especially in war-affected and resource-constrained settings. Objective. To evaluate the effectiveness of the psychological intervention Problem Management Plus (PM+) in reducing symptoms of neurotic and stress-related disorders in adults experiencing psycho-emotional distress. Materials and methods. To assess the effectiveness of PM+, we conducted a content analysis of recent academic literature, including empirical studies, systematic reviews, and meta-analyses. Guidelines from international organizations concerning the use of PM+ in emergency and humanitarian settings were also reviewed. Results and discussion. PM+ is a scalable, low-intensity psychological intervention developed by WHO to support individuals affected by adverse circumstances such as war. Its protocol-based design enables standardization and scalability across diverse contexts. The intervention consists of five weekly individual sessions (each lasting 90 minutes), along with pre- and post-assessment sessions to evaluate client engagement and intervention outcomes on stress levels, emotional state, and overall functioning. Considering the intervention’s alignment with current mental health needs in wartime Ukraine — especially at the community level — our team has initiated a study aimed at improving the emotional well-being of volunteers with neurotic and stress-related symptoms through the PM+ approach. The implementation experience and findings will be presented subsequently. Analysis of international data supports the effectiveness of PM+ in alleviating psychological distress. For example, the STRENGTHS project evaluated low-intensity psychological interventions among Syrian refugees in Europe and the Middle East. In the Netherlands, a randomized controlled trial assessed the peer-delivered PM+ intervention among Syrian adults (<a href="https://www.cambridge.org/core/journals/epidemiology-and-psychiatric-sciences/article/peerprovided-problem-management-plus-pm-for-adult-syrian-refugees-a-pilot-randomised-controlled-trial-on-effectiveness-and-costeffectiveness/0919ADD41B1E37EC70E60886653BE5A8">de Graaff et al., 2020). The study included 60 participants with elevated psychological distress and impaired daily functioning. Three months post-intervention, the PM+ group demonstrated significant reductions in depression (effect size d = 0.52) and anxiety symptoms (d = 0.48) compared to the control group. Statistically significant improvements were also found in PTSD symptoms (d = 0.66, p = 0.006), daily functioning (d = 0.73, p = 0.009), and self-identified problems (d = 0.81, p = 0.005). Health care cost analyses revealed a tendency toward reduced costs in the PM+ group compared to standard care. These findings support the intervention’s effectiveness in reducing distress and improving functioning in individuals facing hardship (<a href="https://www.cambridge.org/core/journals/epidemiology-and-psychiatric-sciences/article/peerprovided-problem-management-plus-pm-for-adult-syrian-refugees-a-pilot-randomised-controlled-trial-on-effectiveness-and-costeffectiveness/0919ADD41B1E37EC70E60886653BE5A8">de Graaff et al., 2020). Group-based PM+ interventions have also shown promising outcomes. One study examined PM+ effects on medical students, revealing reductions in depressive mood and anxiety within this target group (Zhang et al., 2024). Conclusions. The available evidence supports Problem Management Plus as a promising tool for the prevention and correction of neurotic and stress-related disorders in Ukraine, particularly as an adjunct to standard treatment. Further research is essential to adapt and optimize the intervention for the Ukrainian context, considering unique sociocultural factors and wartime challenges.